2020
DOI: 10.1038/s41598-019-57380-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nanoparticle-albumin-bound paclitaxel compared with solvent-based taxanes for metastatic breast cancer: A meta-analysis

Abstract: The curative effects of nanoparticle albumin-bound (nab)-paclitaxel in the first-line treatment of metastatic breast cancer (MBC) are still controversial, with even more after the removal of marketing approval of indication of bevacizumab. Five electronic databases and the related resources were searched for eligible randomized clinical trials (RCTs) without year and language restrictions to perform a meta-analysis. The studies were comparing the efficacy and safety between nab-paclitaxel chemotherapy versus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…[23] Several previous studies have demonstrated that nab-paclitaxel has greater efficacy and a more favorable safety profile (compared with solvent-based paclitaxel) in many malignancies. [13,24,25] To our knowledge, this study is the first to investigate the safety and effectiveness of nab-paclitaxel/ gemcitabine combination chemotherapy in patients with advanced STS. In this retrospective observational study, we observed that nab-paclitaxel was effective for the treatment of STS, with an ORR of 47.1%, and an m-PFS of seven months.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Several previous studies have demonstrated that nab-paclitaxel has greater efficacy and a more favorable safety profile (compared with solvent-based paclitaxel) in many malignancies. [13,24,25] To our knowledge, this study is the first to investigate the safety and effectiveness of nab-paclitaxel/ gemcitabine combination chemotherapy in patients with advanced STS. In this retrospective observational study, we observed that nab-paclitaxel was effective for the treatment of STS, with an ORR of 47.1%, and an m-PFS of seven months.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Several previous studies have demonstrated that nab-paclitaxel has greater e cacy and a more favorable safety pro le (compared with solvent-based paclitaxel) in many malignancies. [13,24,25] To our knowledge, this study is the rst to investigate the safety and effectiveness of nab-paclitaxel/ gemcitabine combination chemotherapy in patients with advanced STS. In this retrospective observational study, we observed that nab-paclitaxel was effective for the treatment of STS, with an ORR of 47.1%, and an m-PFS of seven months.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study indicate that nab-paclitaxel is more effective and has lower toxicity than conventional paclitaxel or docetaxel in STS. In view of the fact that nab-paclitaxel is superior to conventional paclitaxel in the treatment of many malignant tumors, [13,24,25] nab-paclitaxel should not simply be considered as a drug with similar properties to paclitaxel. It should be regarded as a new chemotherapeutic drug; and the e cacy of this drug should be evaluated in various malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…According to clinical data, nab-paclitaxel offers several improvements over conventional, solvent-and Cremophor-based paclitaxel, including lower toxicities, shorter administration time, higher e cacy, and the lack of a need for premedication [23]. Several previous studies have demonstrated that nab-paclitaxel has greater e cacy and a more favorable safety pro le (compared with solvent-based paclitaxel) in many malignancies [13,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study indicate that nab-paclitaxel is more effective and has lower toxicity than conventional paclitaxel or docetaxel in STS. In view of the fact that nab-paclitaxel is superior to conventional paclitaxel in the treatment of many malignant tumors [13,24,25], nab-paclitaxel should not simply be considered as a drug with similar properties to paclitaxel. It should be regarded as a new chemotherapeutic drug; and the e cacy of this drug should be evaluated in various malignancies.…”
Section: Discussionmentioning
confidence: 99%